Cueva del Milodon. The hunting grounds of the Patagonian panther - Martin, Fabiana Maria (My University, 2018)
This paper presents information derived from the taphonomic reevaluation of the Hauthal collection from Cueva del Milodon, Ultima Esperanza, Chile. This is a bone assemblage recovered in 1899 and 1900 at that cave and stored at the Museo de La Plata, Argentina. Mylodon darwini, Hippidion saldiasi, Panthera onca mesembrina and Camelidae are among the most important extinct animals represented at the site. These materials were studied and analyzed several times between the end of the 19th and beginning of the 20th Centuries. However, a detailed study with a taphonomic perspective such as the one presented here was lacking. Contrary to most previous evaluations, this analysis shows that an archaeological component can be defended at the end of the Pleistocene on the basis of the presence of cut marks on Hippidion bones. However, Lehmann-Nitsche excellent description of damages recorded on the ground sloth bones, that he attributed to humans, could not be confirmed. Instead, those damages are here interpreted as large carnivore tooth marks. They are concentrated on ground sloth remains and are attributed to Panthera onca mesembrina. It is here suggested that panthers used the cave and surroundings to prey on ground sloths. The study of the marks and their distribution, especially on ground sloth skulls, indicates the use of a hunting strategy which was similar to that used by jaguars (Panthera onca) when hunting large prey. (c) 2016 Elsevier Ltd and INQUA. All rights reserved.
Keywords: cueva del milodon; taphonomy; ground sloth; patagonian panther; carnivores